Eliciting teachers' ICT competence profiles based on usage patterns within learning object repositories - Sergis, S.; Sampson, Demetrios (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. User profiling is a technique aimed at capturing and exploiting significant characteristics of the users towards the provision of personalized services within adaptive systems such as Recommender Systems (RS). In the context of Technology enhanced Learning (TeL), from a teachers' perspective, the unique ICT competence characteristics of individuals have not been considered when providing Learning Object (LO) recommendations, despite their vital contribution to the level of ICT uptake of teachers. Moreover, there is a lack of mechanisms for automatically eliciting and updating such personal characteristics within Learning Object Repositories (LOR) in order to exploit them for enhanced LO recommendations. Towards tackling this issue, this paper proposes a teacher ICT Competence elicitation mechanism utilizing fuzzy logic for inferring teachers' ICT Competences based on their usage patterns within LOR and presents the results of its preliminary accuracy evaluation. The results indicate that the proposed approach provides high accuracy and can, therefore, construct reliable depictions of the teachers' ICT Competence Profiles.